Bullous pemphigoid as a diagnostic and therapeutic challenge with a wide spectrum of dermatological symptoms - Borowy, Przemysław; Wcisłek, Olga; Płonczyńska, Julia; Heba, Mateusz; Batko, Bogdan (Dermatology Review/Przegląd Dermatologiczny, 2024)
Bullous pemphigoid (BP) is a chronic autoimmune skin disease. It is characterized by the presence of well-tense blisters in the area of erythematous-oedematous eruptions, as well as in the unaffected skin that often develops lesions triggered by medications or focal points. The treatment involves the use of topical or systemic glucocorticosteroids (GCS) and, in challenging cases, immunosuppressive drugs. In a 74-year-old patient with internistic and psychiatric burdens, and oral lesions present for the several past months. BP was diagnosed in surgical biopsies based on immunohistopathological results and specific antibody detection. The case presents diagnostic challenges and various forms of topical therapy in a patient with multiple diseases responsible for limited access to recommended drugs.